The Effect of Ciplukan (Physalis minima) Leaf Extract on Mesenchymal Stem Cell Proliferation and Population Doubling Time (PDT) In Vitro - Irma Suryani; Kartini Eriani; Suhartono Suhartono (Biosaintifika: Journal of Biology & Biology Education, 2022)
Physalis minimahas been used as herbal medicine because it is believed by the community to cure neurodegenerative and cardiovascular diseases. This study aims to determine the effectiveness of P.minima extract in increasing the proliferation of mesenchymal stem cells (MSC) from mouse (Musmusculus) bone marrow (BM). BM from the femur and tibia were isolated using a flushing method. BM-MSC primary culture was conducted in mesenPROÒ medium at 37ᵒC in a 5% CO2 incubator until it reached a 70% confluence.BM-MSCs were sub-cultured overnight in Dulbecco's Modified Eagle's Media (mDMEM). The mDMEM was replaced with a treatment medium on the second day of subculture. The treatment medium was changed every three days and evaluated under an inverted microscope by counting the number of cells at the beginning and the end of the incubation period. The proliferation rate is expressed as PDT, which was statistically analyzed using ANOVA at a significance level of 0.05% and followed-up with Duncan's test. Statistically, P. minima leaf extract could significantly reduce the PDT value. The optimum dose of P. minima leaf extract that can increase the proliferation of BM-MSC was 0.8 mg/ml. It is concluded that P. minima leaf extract was effective as an inducer of BM-MSC proliferation. The data obtained is the preliminary data on the use of P.minimaextracts in stem cell-based therapy. The results of this study provide important information in scientifically proving the potential of P. minima extract on stem cell proliferation.